Fabrizio Rossi Prodi Fabio Capanni due scuole - Appunti di scuola - Rossi Prodi, Fabrizio (Firenze Architettura, 2018)
Every project is type and location. The type is a resistant structure, it is the result of its own history based on the program, but above all on the different cultural phases that have accompanied its evolution. The different issues in the design of today’s school are the result of the long lasting stratification of architectural thinking about its organization.